Treatment of resistant pruritus from cholestasis with albumin dialysis: Combined analysis of patients from three centers. - Parés, Albert; Herrera-Gutiérrez, Manuel Enrique; Avilés, Juán; Sanz, Miquel; Más, Antoni (Elsevier, 2010)
Background & aims: Albumin dialysis using molecular adsorbent recirculating system (MARS) is a new procedure for treating resistant pruritus from cholestasis, but it is usually published as a case report or a short series. Therefore, we analyzed patients with resistant pruritus treated with MARS from three centers, to assess the changes on pruritus and the indices of cholestasis. Methods: Twenty patients (12 female, mean age: 51+/-3.4 years) with chronic cholestatic liver disease or chronic liver-graft rejection were evaluated. The severity of pruritus was assessed using a visual analogue scale (VAS) before and after treatment, and 30 days thereafter. Liver tests, including total bilirubin, alkaline phosphatase, gamma-glutamyl-transferase, cholesterol, triglycerides, and total bile acid were also determined, as well as the number of sessions and the coupled procedure (dialysis or perfusion). Results: Albumin dialysis resulted in a decrease of pruritus (VAS: from 70.2+/-4.8 to 20.1+/-4.2, p<0.001), which partially resumed after 30 days (38.7+/-6.6). VAS decreased by 72% immediately after treatment and by 51% after 1 month. Pruritus decreased in all but one patient. MARS resulted in a significant bile acid decrease of 41% after treatment and by 37% after 1 month. The effect of MARS on pruritus and markers of cholestasis was similar in patients with different diseases and was independent of the coupled procedure. The improvement of pruritus in individuals was positive in 75% of patients. No major adverse effects were observed. Conclusions: Albumin dialysis using MARS is an effective procedure for managing resistant pruritus in most patients with chronic cholestasis and graft rejection.
https://openpolicyfinder.jisc.ac.uk/id/publication/13959
Keywords: Hígado - Trasplante; Hígado - Enfermedades; Albúminas; Diálisis; Hemofiltración; Trasplante de órganos, tejidos, etc. - Complicaciones y secuelas; Prurito; Albumins / therapeutic use; Dialysis Solutions / therapeutic use; Graft Rejection / complications; Hemofiltration / methods; Pruritus / therapy; Liver transplantation